Oxidação eletroquímica de 5-hidroximetilfurfural e glicose: adsorção em Pt (111) e Pt (110) e fotocatálise em BiVO4 - Moreti, Lauren dos Santos (2023)
The exponential increase in energy demand has generated the need to develop more efficient methods based on renewable energy sources. One way to achieve this goal is storing the solar energy through chemical bonds, with emphasis on the production of H2 from water. Despite several advantages, obtaining H2 from water presents obstacles, especially in relation to oxidation processes, which can be avoided with the use of small organic molecules. In addition to providing electrons and protons for the formation of H2, the oxidation of organic molecules also makes it possible to obtain value-added products. Thus, the present dissertation presents a study on the interaction of glucose and 5-hydroxymethylfurfural with model surfaces – Pt(111) and Pt(110) – and with BiVO4 semiconductors modified with Zr, Mo and Pt. It was observed that the current density for glucose oxidation is proportional to the concentration and that the greatest activity occurs for Pt(111). However, on the two single crystalline surfaces, there was a high poisoning of the reactive sites throughout the voltammetric cycles, and this effect was more intense in Pt(110). It was also measured that the adsorption potential of the species has little influence on the charge obtained in the voltammograms after 10 cycles, but the maximum potential of each voltammetric cycle strongly influences the stability and charge of the cycles. 5-HMF generated a higher degree of poisoning than glucose, saturating both surfaces at concentrations of the order of 10-4 mol L-1. In order to reduce the poisoning caused by the interaction of organic molecules with Pt, a photoelectrochemical system containing BiVO4 (ZrMo) superficially modified with Pt was used. It was observed that Pt increases the charge by 24% and decreases the onset potential by 70 mV for glucose oxidation. The main advantage of the photoelectrochemical system was the stability of the current during one hour at fixed potential. However, the same effect was not observed in the presence of 5-HMF, which showed lower activity than water oxidation.